Can Standardizing Applicant High School and Neighborhood Information Help to Diversify Selective Colleges?. (September 2022) - Mabel, Zachary; Hurwitz, Michael D.; Howell, Jessica; Perfetto, Greg
Many selective colleges consider the backgrounds of applicants to improve equity in admissions. However, this information is usually not available for all applicants. We examine whether the chances of admission and enrollment changed after 43 colleges gained access to a new tool that standardizes information on educational disadvantage for all applicants. Applicants from the most challenging school and neighborhood backgrounds experienced a 5-percentage point increase in the probability of admission in the year of adoption relative to similar applicants in the previous year. The tool did not alter the probability of enrollment as a function of applicant challenge level in the full sample, but positive changes are concentrated among applicants to institutions that used the tool to allocate financial aid.